The Role Of Nurses In Terminal Patient Care In Palliative Units - Isrofah; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
ABSTRACT Palliative care is an approach aimed at improving the quality of life for terminally ill patients. Nurses play a crucial role in providing holistic care encompassing physical, psychological, social, and spiritual aspects. This study aims to analyze the role of nurses in caring for terminally ill patients in a palliative care unit. The research method used a qualitative approach with a descriptive design. Data were obtained through in-depth interviews with 10 nurses in the palliative care unit. The results indicate that nurses act as direct caregivers, educators , communicators, and emotional supporters for patients and their families. Challenges faced include emotional burden and limited resources. It is concluded that the role of nurses is crucial in improving the quality of life for terminally ill patients. Keywords: Nurses, Palliative Care, Terminal Patients, Quality of Life